No Impact of Cerebellar Anodal Transcranial Direct Current Stimulation at Three Different Timings on Motor Learning in a Sequential Finger-Tapping Task - Nguemeni, Carine; Stiehl, Annika; Hiew, Shawn; Zeller, Daniel (Frontiers in Human Neuroscience, 2021)
Abstract Background: Recently, attention has grown toward cerebellar neuromodulation in motor learning using transcranial direct current stimulation (tDCS). An important point of discussion regarding this modulation is the optimal timing of tDCS, as this parameter could significantly influence the outcome. Hence, this study aimed to investigate the effects of the timing of cerebellar anodal tDCS (ca-tDCS) on motor learning using a sequential finger tapping task (FTT). Methods: 122 healthy young, right-handed subjects (96 females) were randomized into four groups (Duringsham, Before, Duringreal, After). They performed two days of FTT with their non-dominant hand on a custom keyboard. The task consisted of 40s of typing followed by 20s rest. Each participant received ca-tDCS (2 mA, sponge electrodes of 25 cm2, 20 min) at the appropriate timing and performed 20 trials on the first day (T1, 20 min). On the following day, only 10 trials of FTT were performed without tDCS (T2, 10 min). Motor skill performance and retention were assessed. Results: All participants showed time-dependent increase in learning. Motor performance was not different between groups at the end of T1 (p=0.59). ca-tDCS did not facilitate the retention of the motor skill in the FTT at T2 (p=0.27). Thus, our findings indicate an absence of effect of ca-tDCS on motor performance or retention of the FTT independently from the timing of stimulation. Conclusion: The present results suggest that the outcome of ca-tDCS are highly dependent on the task and stimulation parameters. Future studies need to establish clear basis for successful and reproducible clinical application of ca-tDCS.